Paxlovid: development, pharmacology and implications for pharmaceutical practice (Research, Society and Development, 2023)
Paxlovid is an oral medication consisting of two active principles, nirmatrelvir and ritonavir, which act by preventing the viral replication of Sars-CoV-2 through the reversible inhibition of the 3Clpro protease. Developed in a short period of time by Pfizer, paxlovid was temporarily authorized on an experimetal basis by ANVISA for the treatment of Covid-19 in adults who do not require the use of supplemental oxygen and who are at high risk of developing serious complications. Thus, the objective of the work was to present a review of paxlovid in the treatment of Covid-19, an overview of the pharmacological properties, including pharmacodynamics, pharmacokinetics and potential drugs interactions, its development and implications for pharmaceutical practice. This is a literature review of the narrative type, based on the results of a bibliographical research carried out on the PubMed platform between february 18th and 20th, 2023, processed in three stages: identification, screening and inclusion. A total of 708 articles were identified and approximately 3.24% of the total sample was selected for review. The addition of the article Covid-19: pathophysiology and targets for therapeutic intervention was validated, resulting in a final sample of 24 selected articles. With its efficacy, effectiveness and safety well clarified by several clinical studies and in the light of pharmacology, paxlovid represents a fundamental tool in the fight against the Sars-CoV-2 virus, however, the pharmacist must perform a critical management, considering the risk and the potential for pharmacological interactions between paxlovid and other drugs.